Pengaruh Emotional Freedom Technique (EFT) Terhadap Kecemasan Pada Pasien Chronic Kidne Disease (CKD) - Ni Made Nopita Wati; Ni Luh Putu Thrisna Dewi (HB PRESS, 2021)
Chronic kidney disease (CKD) and haemodialysis (HD) as an incident which causes a negative emotion experience which is called stressor. A well taken care stressor makes a person grows mature. On the contrary, a stressor that is not taken care well causes a physiological response such as worry, depression, angry, fear, feeling guilty, even death. A dismay is a feeling of worry, an unclear fear. Dismay is also a big power in controlling behaviour, good behaviour or disturb behaviour. The purpose of this research is to find out the influence of emotional freedom technique (eft) to the level of CKD patient’s dismay. Method: quasi experiment pre and post with control Group design i.e. the research design is divided into 2 groups One group as an intervention group and the other group as a control group. Result: there is a different level of dismay of CKD patient Before and after being given an emotional freedom technique (eft) to intervention and control group, where in the group shows that the p value is 0,000 while on control group the p value is 1,000. Based on physiologies technique this therapy knock the meridian body spots that stimulate relaxation effect from inside the body naturally, therefore when the body is relax the mind is more calm, indirectly contribute in decreasing the worry level of the patient because of uncontrolled excessive feeling.Conclusion: EFT is consider as an effective therapy, easy and fast in handling the physiological aspect especially dismay in CKD patient.